2000
DOI: 10.1007/s004350000027
|View full text |Cite
|
Sign up to set email alerts
|

The duct connecting Malpighian tubules and gut: an ultrastructural and comparative analysis in various Ephemeroptera nymphs (Pterygota)

Abstract: Malpighian tubules proper are connected to the gut by ducts called trunks, the organization of which is described at ultrastructural level in the nymphs of various mayfly species, namely Ecdyonurus venosus (Heptageniidae), Ephemerella ignita (Ephemerellidae), Choroterpes picteti (Leptophlebiidae), and Caenis luctuosa (Caenidae). Trunks are luminal tubes varying in arrangement, number, shape, and length. The main cell type of the trunk wall is represented by cells that are bordered by a thin cuticle along their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Interestingly, MTs of insects (including C. riparius and A. aegypti) are well known to secrete a fluid that is iso-osmotic to the hemolymph; however, it was suggested that the trunk of mayfly nymph MTs has a reabsorptive function aiding in production of hypo-osmotic fluid (Gaino and Rebora, 2000a). This idea is based on ultrastructural studies of the mayfly nymph MT trunk which reported that the cells making up this region are morphologically similar to the cells lining the lumen of the HG (Nicholls, 1983;Martoja and Ballan-Dufrançais, 1984;Gaino and Rebora, 2000a). In insects, the primary site of reabsorption of ions, which in FW insects results in a hypo-osmotic fluid to be excreted, is the HG (Cochran, 1985;Phillips et al, 1986;Bradley, 1987).…”
Section: Fw Mayfly Nymph Hemolymph Ion Compositionmentioning
confidence: 99%
“…Interestingly, MTs of insects (including C. riparius and A. aegypti) are well known to secrete a fluid that is iso-osmotic to the hemolymph; however, it was suggested that the trunk of mayfly nymph MTs has a reabsorptive function aiding in production of hypo-osmotic fluid (Gaino and Rebora, 2000a). This idea is based on ultrastructural studies of the mayfly nymph MT trunk which reported that the cells making up this region are morphologically similar to the cells lining the lumen of the HG (Nicholls, 1983;Martoja and Ballan-Dufrançais, 1984;Gaino and Rebora, 2000a). In insects, the primary site of reabsorption of ions, which in FW insects results in a hypo-osmotic fluid to be excreted, is the HG (Cochran, 1985;Phillips et al, 1986;Bradley, 1987).…”
Section: Fw Mayfly Nymph Hemolymph Ion Compositionmentioning
confidence: 99%
“…Mayflies in particular are highly sensitive to ionic stress as they regulate their ion uptake and release using specialized structures within their gills, their integument, and internally via Malphigian tubules. 83 For these sensitive taxa, large increases in certain ions can disrupt water balance and ion exchange processes and cause stress or death. Tests for conductivity toxicity for mayflies have often proved inconclusive, 82,84-87 yet these studies are typically based on lab toxicological tests with hardy organisms that are easy to rear in lab settings (i.e., Hexagenia, Centroptilum, Cloeon, Isonychia) and are likely to be less sensitive than the mayfly genera that appear especially susceptible to ionic stress (e.g., ephemerellids, heptageniids).…”
Section: Longitudinal Impactsmentioning
confidence: 99%
“…This is particularly important for aquatic insects with high cuticular permeability. Mayflies in particular are highly sensitive to ionic stress as they regulate their ion uptake and release using specialized structures within their gills, their integument, and internally via Malphigian tubules 83 . For these sensitive taxa, large increases in certain ions can disrupt water balance and ion exchange processes and cause stress or death.…”
mentioning
confidence: 99%
“…The Malpighian tubules of mayfly nymphs have also been investigated in the context of osmoregulation, but we do not have a clear understanding of their function. The morphological structure of the Malpighian tubules in mayfly nymphs is comparatively complex (Gaino and Rebora, 2000a). The distal portions of the tubules are coiled to varying extents, and connect to the gut either directly or through connecting tubes and trunks (Gaino and Rebora, 2000a,b;Nicholls, 1983;Nowghani et al, 2017).…”
Section: Midgut Gastric Caecae and Malpighian Tubulesmentioning
confidence: 99%